2017
DOI: 10.1017/ice.2017.209
|View full text |Cite
|
Sign up to set email alerts
|

Patient Safety Culture and the Ability to Improve: A Proof of Concept Study on Hand Hygiene

Abstract: OBJECTIVE To investigate whether the safety culture of a hospital unit is associated with the ability to improve. DESIGN Qualitative investigation of safety culture on hospital units following a before-and-after trial on hand hygiene. SETTING VU University Medical Center, a tertiary-care hospital in the Netherlands. METHODS With support from hospital management, we implemented a hospital-wide program to improve compliance. Over 2 years, compliance was measured through direct observation, twice before, and 4 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 35 publications
(64 reference statements)
5
29
0
3
Order By: Relevance
“…By analyzing the information in Table 6, the correlation between the status of operating room standards and safety culture was evaluated positively. This result is consistent with the paper by , Safazadeh and Zarei, Behzadi et al [29], And Caris et al [25]. In explaining this result, it can be said that the operating room is a sector that pursues specific goals, and since this sector is particularly concerned with people's health and the community is particularly sensitive to it, safety performance and safety culture in This unit has a great role to play.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By analyzing the information in Table 6, the correlation between the status of operating room standards and safety culture was evaluated positively. This result is consistent with the paper by , Safazadeh and Zarei, Behzadi et al [29], And Caris et al [25]. In explaining this result, it can be said that the operating room is a sector that pursues specific goals, and since this sector is particularly concerned with people's health and the community is particularly sensitive to it, safety performance and safety culture in This unit has a great role to play.…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that continuous training and development, support from hospital management, managerial / supervisory expectations, error feedback and communication, teamwork, and hospital handover were among the predictors of patient safety culture. Caris et al [25] examined patient safety culture using the HSOPSC questionnaire. The results of their work showed that organizational learning and continuous improvement are accompanied by negative attitude of nurses and need to create a positive safety culture with free communication, mutual belief, shared understanding of the importance of safety and taking preventive measures in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Caris und Kollegen berichteten 2017 davon, dass sich bei "niedrig-qualitativer" Sicherheitskultur durch Händehygiene-Programme nur unbefriedigende Verbesserungen auf entsprechenden Stationen erzielen ließen. Dahingegen wiesen Stationen mit hoch-qualitativer Sicherheitskultur deutliche Compliance-Steigerungen auf [40].…”
Section: Stefan Bushuvenunclassified
“…2,3 To date guidelines, policy, and education initiatives have broadly yielded little sustained behavioural change. 4,5,6 Studies however do support performance being impacted by culture in healthcare. 7,8 The influence of the healthcare culture on infection control practice has not been explored 9 even though studies show association between patient outcomes and culture.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The influence of the healthcare culture on infection control practice has not been explored 9 even though studies show association between patient outcomes and culture. 4,3,10 This paper discusses the cultural milieu of infection prevention and control (IPC) practice and embedded norms, proposing a cultural shift is mandatory to address suboptimal IPC practice. not for citation purposes Suboptimal infection prevention and control in the healthcare culture Cioffi each other.…”
Section: Introductionmentioning
confidence: 99%